Manfaat Haji Perspektif Ekonomi Mikro dan Makro - Agus Syafei; Anton Bawono (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractThe purpose of this research is to find out some of the benefits of performing the pilgrimage from a micro and macro economic perspective. Research using descriptive qualitative methods is expected to reveal the benefits of performing the pilgrimage as implied in QS Al Hajj: 28 in a more comprehensive manner. The results of the study concluded that the implementation of the pilgrimage greatly influences both the micro and macro economic sectors, but has not been explored other than the management of the Hajj funds carried out by the Hajj Financial Management Agency.Keywords: Benefits, Hajj, Micro and Macroeconomics